Encrypted quick response scheme for hotel check-in and access control system - Cheong, S.; Ling, Huo Chong; Teh, P.; Ahmed, P.; Yap, W. (SAGE PUBLICATIONS INC, 2017)
The unpleasant experience of long queue while waiting to check-in at hotel is a common problem faced by guests especially during holidays. As such, various self-service technologies (SSTs) were introduced over the years by researchers with the aim to increase the avenues of checking-in guests. Self-check-in kiosk is an invention that allows guests to check-in themselves using bar codes that were sent to them in advance. Although bar codes are able to reduce guests’ waiting time, it cannot be used to unlock hotel rooms. This makes mobile device a better medium for hotel check-in and access control system. Despite mobile device is very convenient and easy to operate, guests would have to own the specific type of mobile device such as near-field communication smartphone and its customized application before using the system. This makes the solution not user-friendly to guests. Therefore, a novel encrypted quick response scheme is presented to extend the existing SST to unify the process of check-in and room access control. The proposed scheme uses quick response codes and cryptography techniques to generate secure hotel keys that can be printed or stored inside a smartphone, thus, supporting a wide range of guests.